2003
DOI: 10.3171/jns.2003.99.2.0291
|View full text |Cite
|
Sign up to set email alerts
|

Surgical experience in 130 pediatric patients with Chiari I malformations

Abstract: The authors believe this to be the largest reported series of pediatric patients who have undergone posterior fossa decompression for Chiari I malformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
185
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 288 publications
(197 citation statements)
references
References 59 publications
3
185
2
7
Order By: Relevance
“…Re- ported rates of scoliosis vary in the literature. In a series of 130 patients, Tubbs et al 13 demonstrated that 18% of those with CM-I presented with concurrent scoliosis. It is not clear why our series shows a lower percentage of patients with scoliosis, although it may be due to regional differences or our referral pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Re- ported rates of scoliosis vary in the literature. In a series of 130 patients, Tubbs et al 13 demonstrated that 18% of those with CM-I presented with concurrent scoliosis. It is not clear why our series shows a lower percentage of patients with scoliosis, although it may be due to regional differences or our referral pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Tubbs et al [11][12][13] reviewed 130 symptomatic pediatric Chiari I malformation patients and 22 of them were Chiari 1.5 malformation patients. Clinical manifestations and symptomatic outcomes were similar between the two groups in terms of degree of tonsillar herniation (Chiari I malformation vs. Chiari 1.5 malformation : 7 mm vs. 12.7 mm), the angulation of the odontoid process (98.0˚vs.…”
Section: Discussionmentioning
confidence: 99%
“…This theory indicates an alteration in cerebrospinal fluid (CSF) circulation and relative obstruction of CSF flow at the foramen magnum 9) . Presumably, an intermittent vector of force then develops with each Valsalva maneuver, which can lead to the progressive downward movement of developing tissue through the foramen magnum 12) . In the present case, the patient was incidentally found to have tonsillar herniation and mild ventriculomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologic deficit prior to the onset of treatment indicates an increased possibility of additional injury. This situation has been reported to be suggestive of brain stem and intraspinal anomalies [12][13][14][15][16][17][18]. In these patients, who have chronic ischemia and hypoxia of the spinal cord due to the spinal deformities, ''sick spinal cord'' which together with the abnormalities of the spinal cord or the canal, distraction or compression of the spinal cord following corrective maneuvers for the curve may lead to Fig.…”
Section: Clinical Factorsmentioning
confidence: 99%